Application of Private International Law Instruments in the Recognition of Marriages by Shariah Court in Malaysia - Helmi Md Said, Muhamad; Ahamat, Haniff; Abdul Hak, Nora; Md Hashim, Noraini; Che Soh Yusoff, Roslina (International Journal of Engineering and Technology, 2018)
In recent years, the phenomenon of cross-border marriage has provoked an increase of international disputes in family relationship. In Malaysia, due to growing cross-border marriage, the Shariah Court in Malaysia cannot avoid and they have been forced to react to this situation. Patterns and characteristics of cross-border marriage have varied widely among world regions and races and therefore need theoretical enlightenments. The ideals of marriage which may reflect in husbands and wives thinking of living happily ever after may easily be stumped by the realities of life when problems arise. Due to the increasing number of cross-border marriage and very limited research on the international dimensions of the law regulating peculiar aspects of marriages, this paper aims to discuss the application of rules of private international law in the Malaysian Shariah courts affecting recognition of cross-border marriage. In this study, data was obtained from materials consisting of textbooks, legal cases, legislation, journals, magazines, newsletters, newspapers, seminar and conference papers and unpublished writings (dissertations and theses). This paper involves investigation and analysis of the materials available in the library. Hence, it uses the historical, analytical and comparative methods. This article is a preamble to a more detailed study of the International marriages which the result will be useful for further improvement of the existing legal provisions in Malaysia.